Theory and data in cognitive linguistics - Gisborne, Nikolas, 1966-; Hollmann, Willem (Benjamins current topics, 2014)
How do people describe events they have witnessed? What role does linguistic aspect play in this process? To provide answers to these questions, we conducted an experiment on aspectual framing. In our task, people were asked to view videotaped vehicular accidents and to describe what happened (perfective framing) or what was happening (imperfective framing). Our analyses of speech and gesture in retellings show that the form of aspect used in the question differentially influenced the way people conceptualized and described actions. Questions framed with imperfective aspect resulted in more mo.